Employing Renal Function in Determining Ribavirin Dosages for Chronic Hepatitis C Patients to Help Ensure Safer Treatment - Oota, Masatoshi; Maruhashi, Akira; Ishii, Yoshiyuki; Maeda, Yorinobu; Kiribayashi, Yoshie; Murakami, Teruo; Takano, Mikihisa; Moriya, Takashi (Iryo Yakugaku (Japanese Journal of Pharmaceutical Health Care and Sciences), 2004)
The daily dose of ribavirin is currently determined on the basis of patient body weights. However, this is not considered to be adequate theoretically, since total plasma clearance of ribavirin (CLtotal) is due to hepatic metabolism and renal excretion. Recently, we proposed that the dosage of ribavirin be determined on the basis of renal function and body weight as the result of analyzing clinical data for 19 Japanese chronic hepatitis C patients. Thereafter, data were obtained for additional chronic hepatitis C patients (31 males and 16 females) and we re-evaluated the feasibility of using renal function for the determination of ribavirin dosage in the present study. A steady-state trough plasma concentration (Cpss) was achieved for ribavirin approximately 4 weeks after the initiation of treatment. There was marked variation in Cpss values among patients, and high ribavirin concentrations (>3500ng/mL) caused red blood cell disorders, as evaluated from plasma hemoglobin levels. Calculated as daily dose/body weight/trough Cpss, CLtotal for ribavirin was well correlated with the creatinine clearance (CLcr) of patients, and it was also well correlated with body weight, age, serum creatinine (S-Cr) and alanine aminotransferase (ALT) levels. This would indicate that CLtotal for ribavirin normalized by body weight is dependent on the renal function of the patient. Also, a linear relationship was observed between the predicted Cpss, which was estimated from body weight, dose and CLcr, and the observed Cpss (Observed Cpss=1.02×Predicted Cpss+27.71, 10 patients, r=0.6585). In conclusion, the determination of ribavirin dosages on the basis of renal function and body weight, rather than body weight alone, could be a better method of obtaining the plasma levels of ribavirin desired for achieving effective and safe treatment.